Pain Associated with Endometriosis. A Review of Quality of Life. Psychological Aspects, Career Development, Sexual Health, and Intimate Partner Relationships - Zubiak, Marlena; Byrska, Martyna; Barska-Kobylińska, Hanna; Langner, Sara; Malaka, Ewa Katarzyna; Janura, Marta; Elias, Jagoda; Biesiada, Wiktor; Szydłowska, Sara; Błaszków, Krzysztof (Quality in Sport, 2025)
Introduction: Endometriosis is a chronic estrogen-dependent inflammatory disease characterized by the presence of tissue resembling the endometrium outside the uterine cavity. It affects approximately 10% of women of reproductive age. The main symptoms include severe pain, reduced fertility, and sexual dysfunction. Treatment includes pharmacotherapy and surgical interventions, depending on the severity of symptoms, the location of lesions, and their extent. Study Objective: The aim of the study was to assess quality of life, as well as the impact of dyspareunia and other endometriosis-related symptoms on sexual health and intimate partner relationships. Materials and Methods: Over 60 scientific articles addressing this issue were analyzed. The studies were retrieved from the PubMed platform, spanning the years 2004 to 2024. Conclusions: The symptoms of endometriosis, along with limited therapeutic options, significantly affect overall quality of life, sexual health, and partner relationships. Based on the available literature and current knowledge, it can be concluded that it is crucial to provide not only medical treatment but also sexological and psychological support.